2020
DOI: 10.1101/2020.08.06.226779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The DNA mimic protein BCAS0292 is involved in the regulation of virulence ofBurkholderia cenocepacia

Abstract: Adaptation of opportunistic pathogens to their host environment requires reprogramming of a vast array of genes to facilitate survival in the host. Burkholderia cenocepacia, a Gram-negative bacterium that colonizes environmental niches, is exquisitely adaptable to the hypoxic environment of the cystic fibrosis lung and survives in macrophages. B. cenocepacia possesses a large genome encoding multiple virulence systems, stress response proteins and a large locus that responds to low oxygen. We previously identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This is due to the presence of the HU protein, which plays a crucial part in the organization and compaction of DNA in D. radiodurans . P. fungorum was also determined to be a highly UV resistant microbe, and while there is no published literature to support the existence of HU protein in P. fungorum , it has been shown that Paraburkholderia cenocepacia (a closely related strain) expresses HU protein [ 40 ]. Therefore, DNA compaction found within the nucleoid of both P. fungorum and D. radiodurans may facilitate a tolerance to DNA degradation caused by freeze-thaw conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the presence of the HU protein, which plays a crucial part in the organization and compaction of DNA in D. radiodurans . P. fungorum was also determined to be a highly UV resistant microbe, and while there is no published literature to support the existence of HU protein in P. fungorum , it has been shown that Paraburkholderia cenocepacia (a closely related strain) expresses HU protein [ 40 ]. Therefore, DNA compaction found within the nucleoid of both P. fungorum and D. radiodurans may facilitate a tolerance to DNA degradation caused by freeze-thaw conditions.…”
Section: Discussionmentioning
confidence: 99%